Tuning the sub-processes in laser reduction of graphene oxide by adjusting the power and scanning speed of laser. (January 2019) - Wan, Zhengfen; Wang, Shujun; Haylock, Ben; Kaur, Jasreet; Tanner, Philip; Thiel, David; Sang, Robert; Cole, Ivan S.; Li, Xiangping; Lobino, Mirko; Li, Qin
Abstract: Laser reduction of graphene oxide is a promising technology for manufacturing advanced devices such as supercapacitors, sensors and transistors, owing to its distinctive advantages in selective and localized GO reduction, direct micro-nanoscale patterning, and no requirement for chemicals. However, the fundamental mechanism underlying the laser induced reduction is still not well understood. In this paper, we demonstrate that by adjusting the power and scanning speed of a 780 nm femtosecond laser, not only can one distinguish, but also effectively tune, two coexisting sub-processes during the laser reduction, namely the direct conversion from sp 3 to sp 2 carbon and removal of oxygen functional groups. Different oxygen containing groups demonstrate varied degrees of reduction when the power of the laser was varied. Our study provides solid and direct evidence for the coexistence of two sub-processes in the laser induced reduction of graphene oxide, which is essential for both mechanistic understanding and practical adoption of this technique in real word applications. Graphical abstract: Image 1